2018
DOI: 10.1371/journal.pone.0199981
|View full text |Cite
|
Sign up to set email alerts
|

Do outpatient statins and ACEIs/ARBs have synergistic effects in reducing the risk of pneumonia? A population-based case-control study

Abstract: Whether statins and an angiotensin-converting enzyme inhibitors (ACEIs) / angiotensin receptor blockors (ARBs) are associated with reduced risks of infection events is still inconclusive. This study aimed to explore the risk of hospitalization for pneumonia among patients who had received treatment with ACEIs/ARBs and/or statins using a population-based dataset. This study included 19,281 patients as cases who were hospitalized for pneumonia and 19,281 controls. We used a logistic regression to compute the odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…18 In addition, ACEIs and ARBs have been also previously linked to reduced mortality in patients with CAP 19 and a reduced risk for CAP requiring hospitalization. 20 In summary, available studies do not provide sound evidence that hypertension is an independent risk factor for LRTI/CAP. However, they indicate that hypertension contributes to the increased occurrence of incident cardiovascular events in these patients, in agreement with the well-established risk associated with hypertension.…”
Section: Antihypertensive Treatment and Lrtismentioning
confidence: 97%
“…18 In addition, ACEIs and ARBs have been also previously linked to reduced mortality in patients with CAP 19 and a reduced risk for CAP requiring hospitalization. 20 In summary, available studies do not provide sound evidence that hypertension is an independent risk factor for LRTI/CAP. However, they indicate that hypertension contributes to the increased occurrence of incident cardiovascular events in these patients, in agreement with the well-established risk associated with hypertension.…”
Section: Antihypertensive Treatment and Lrtismentioning
confidence: 97%
“…Concomitantly, recent studies have suggested that the clinical benefits associated with these drugs may be attributed to their role in the upregulation of ACE2 expression and activity [ 120 , 125 ]. Clinical studies using a large cohort of patients have shown that patients treated with ACE inhibitors and ARBs had a lower risk of developing pneumonia [ 126 ] and ARDS [ 34 ]. From a cardiopulmonary perspective, no clear indication or data is supporting the benefits of discontinuing or holding the use of RAS antagonists in these patients.…”
Section: Potential Therapies For Covid-19mentioning
confidence: 99%
“…The conflicting data among studies might be related to heterogeneous regimens, timing of treatment with statins, variability in definition of pneumonia, and study duration. 56 Patients with acute ischemic stroke in the present study, who were particularly at great risk for pneumonia, may be more likely to benefit from treatment with statins than the general population. To date, no large randomized clinical study has been conducted evaluating the effect of statins on the development of pneumonia as the primary outcome measure.…”
Section: Discussionmentioning
confidence: 70%